(untitled) (Journal of Comparative Social Work, 2011)
Much social work practice with adolescents involved in activities known to be risky, such as experimentation with substances or petty crime, seems to have been influenced by the conventional input-output model which assumes an unreflected relationship between the present manifestation of risk and adverse future outcomes. This model relies on an uncertain scientific basis and does not really allow for the adolescents’ own reflexivity. This article aims at contributing to the shaping of more reflexive concepts for social work in this area, and is based on material derived from a focus group made up of 17 adolescents from Central Norway, aged 16-18 years old. The major foci of analysis were: i) how the adolescents positioned themselves with regard to conflicting notions of respectability, ii) which constructions of meaning might be attached to this positioning and iii) how the positioning might inform social work practice.